Effects of Puffing, Acid, and High Hydrostatic Pressure Treatments on Ginsenoside Profile and Antioxidant Capacity of Mountain-Cultivated Panax ginseng - Jang-Hwan Kim; Jae-Sung Shin; Wooki Kim; Hyungjae Lee; Moo-Yeol Baik (Foods, 2023)
The purpose of this study was to investigate the effects of puffing, acid, and high hydrostatic pressure (HHP) treatments on the ginsenoside profile and antioxidant capacity of mountain-cultivated Panax ginseng (MCPG) before and after treatments. Puffing and HHP treatments decreased extraction yield and increased crude saponin content. The combination of puffing and HHP treatment showed significantly higher crude saponin content than each single treatment. Puffing treatment showed the highest ginsenoside conversion compared with HHP and acid treatments. Significant ginsenoside conversion was not observed in HHP treatment but was in acid treatment. When the puffing and acid treatments were combined, Rg3 and compound K content (1.31 mg and 10.25 mg) was significantly higher than that of the control (0.13 mg and 0.16 mg) and acid treatment (0.27 mg and 0.76 mg). No synergistic effect was observed between acid and HHP treatments. In the case of functional properties, the puffing treatment showed a significant increase in TFC (29.6%), TPC (1072%), and DPPH radical scavenging capacity (2132.9%) compared to the control, while acid and HHP combined treatments did not significantly increase; therefore, the synergistic effects of HHP/puffing and acid/puffing treatments were observed in crude saponin content and ginsenoside conversion, respectively. Consequently, puffing combined with acid or HHP treatments may provide new ways to produce high-value-added MCPG with a higher content of Rg3 and compound K or crude saponin compared to untreated MCPG.